Corporate social responsibility and marketing: A bibliometric and visualization analysis of the literature between the Years 1994 and 2020 - Quezado, T. (2022)
Several studies explored the effect of Corporate Social Responsibility (CSR) on marketing. However, bibliometric research that organizes this production is scarce. Thus, this study aims to provide a bibliometric view of marketing-related CSR research, identifying this ﬁeld’s state-of-the-art literature. Two thousand and forty-two articles were collected through the Web of Science (WoS) platform. Data were analyzed using VOSviewer software to map the data graphically. The results show that: (a) the literature on CSR in the marketing area is growing; (b) ﬁve articles alone accounted for 9940 citations, and there are several proliﬁc authors; (c) the prominent journals identiﬁed in this research published 42.16% of the total; (d) The “Journal of Business Ethics” is the leader in the number of publications, followed by “Sustainability,” which has shown strong growth in recent years, and; (e) The US is the leading country, according to the number of articles and citations. The keyword trending network analysis revealed that CSR is becoming a strategic marketing approach for companies. This study offers an insight into the state-of-the-art and trends identiﬁcation in CSR and marketing.